Remdesivir is a direct-acting antiviral that inhibits RNA-dependent RNA polymerase from severe acute respiratory syndrome coronavirus 2 with high potency - Gordon, Calvin J.; Tchesnokov, Egor P.; Woolner, Emma; Perry, Jason K.; Feng, Joy Y.; Porter, Danielle P.; Götte, Matthias (The Journal of biological chemistry, 2020)
Effective treatments for coronavirus disease 2019 (COVID-19) are urgently needed to control this current pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Replication of SARS-CoV-2 depends on the viral RNA-dependent RNA polymerase (RdRp), which is the likely target of the investigational nucleotide analogue remdesivir (RDV). RDV shows broad-spectrum antiviral activity against RNA viruses, and previous studies with RdRps from Ebola virus and Middle East respiratory syndrome coronavirus (MERS-CoV) have revealed that delayed chain termination is RDV's plausible mechanism of action. Here, we expressed and purified active SARS-CoV-2 RdRp composed of the nonstructural proteins nsp8 and nsp12. Enzyme kinetics indicated that this RdRp efficiently incorporates the active triphosphate form of RDV (RDV-TP) into RNA. Incorporation of RDV-TP at position i caused termination of RNA synthesis at position i+3. We obtained almost identical results with SARS-CoV, MERS-CoV, and SARS-CoV-2 RdRps. A unique property of RDV-TP is its high selectivity over incorporation of its natural nucleotide counterpart ATP. In this regard, the triphosphate forms of 2′-C-methylated compounds, including sofosbuvir, approved for the management of hepatitis C virus infection, and the broad-acting antivirals favipiravir and ribavirin, exhibited significant deficits. Furthermore, we provide evidence for the target specificity of RDV, as RDV-TP was less efficiently incorporated by the distantly related Lassa virus RdRp, and termination of RNA synthesis was not observed. These results collectively provide a unifying, refined mechanism of RDV-mediated RNA synthesis inhibition in coronaviruses and define this nucleotide analogue as a direct-acting antiviral.